Competitive Liner Shipping Network Design. (November 2017) - Vad Karsten, Christian; Brouer, Berit Dangaard; Pisinger, David
Highlights: We present a solution method for the liner shipping network design problem. The algorithm explicitly handles transshipment time limits for all demands. Individual sailing speeds at each service leg are used to balance sailing speed against operational costs. Computational results are showing very promising results for realistic global liner shipping networks. A sensitivity analysis on fluctuations in bunker price confirms the applicability of the algorithm. Abstract: We present a solution method for the liner shipping network design problem which is a core strategic planning problem faced by container carriers. We propose the first practical algorithm which explicitly handles transshipment time limits for all demands. Individual sailing speeds at each service leg are used to balance sailing speed against operational costs, hence ensuring that the found network is competitive on both transit time and cost. We present a matheuristic for the problem where a MIP is used to select which ports should be inserted or removed on a route. Computational results are presented showing very promising results for realistic global liner shipping networks. Due to a number of algorithmic enhancements, the obtained solutions can be found within the same time frame as used by previous algorithms not handling time constraints. Furthermore, we present a sensitivity analysis on fluctuations in bunker price which confirms the applicability of the algorithm.